Freeze drying of food materials is a time and energy consuming process, hence a high cost process. The drying rate is limited by heat and mass transfer process within the dried portion of the product. In order to improve the freeze drying performance, it is important to know parameters which affect the drying characteristics of each spesific food material, in regard to the drying time and the energy consumption. The objective of this experiment was to study the freeze drying characteristic of mi - Yulia Lisnawati; Armansyah H Tambunan (Jurnal Keteknikan Pertanian, 1997)
Freeze drying of food materials is a time and energy consuming process, hence a high cost process. The drying rate is limited by heat and mass transfer process within the dried portion of the product. In order to improve the freeze drying performance, it is important to know parameters which affect the drying characteristics of each spesific food material, in regard to the drying time and the energy consumption. The objective of this experiment was to study the freeze drying characteristic of miched beef especially the effect of freezing rate and surface temperature of the material to the drying time. The study was conducted with freezing rate at 7.71 cmhours and 1.94 cmhours which are classified into fast and slow freezing rate, while the surface temperature of the material was controlled at 40 OC, 35 OC, and 30 OC. The experimental results confirmed that the faster freezing rate then the longest drying time, while the higher surface temperature give a shorter drying time of miched beef. It is important to determine the optimal freezing rate and surface temperature from the view point of energy consumption.